(untitled) (CIPEEX, 2024)
In Brazil, issues such as body self-image and mental health are increasingly discussed, especially in the school environment, where problems such as anxiety, body dissatisfaction and bullying are in evidence. Exposure to the internet and social networks, such as Instagram, intensifies these problems, reinforcing the need for public policies focused on self-esteem, self-care and safety in the school environment. METHODOLOGY: The study is a descriptive experience report, based on the experiences of students on the Medicine course at UniEvangélica, during an integrative week organized by the Family and Community Medicine I module. The project, entitled "QVEscola: promoting health and quality of life in school communities in Anápolis-GO", took place between May 13 and 16, 2024 at Escola Municipal Cora Coralina, focusing on elementary school students. The methodology included questionnaires and various activities, such as workshops on beauty, bullying, obesity, anxiety, sexually transmitted infections, conscious use of screens and planetary health, aiming to promote quality of life among students. RESULTS: Based on the WHO’s expanded health concept, the project implemented six educational activities at the Cora Coralina Municipal School, in Anápolis, Goiás, focused on promoting health and improving quality of life. These educational interventions provided mutual learning between students and participants, significantly contributing to health education in the community and the adoption of healthier behaviors. The impact was visible, especially in the sharing of knowledge acquired between participants and the local community, promoting health in a broad and sustainable way. CONCLUSION: The project proved to be an effective initiative in disseminating expanded health concepts among children and adolescents. The experience reinforced the importance of extension actions in medical training, showing that these activities not only expand students’ learning, but also contribute to the development and strengthening of social responsibility.